Environmentally Friendly Advertising, Green Product Value, and Price Perception on Purchasing Decisions with Environmental Awareness as a Moderating Variable on Eco-Friendly Products in West Java - Syaifuddin Syaifuddin (MIX: JURNAL ILMIAH MANAJEMEN, 2026)
Objective: The global environmental crisis has heightened public awareness of the impact of consumption on environmental sustainability. However, a persistent gap remains between environmental awareness and actual consumer behavior in choosing eco-friendly products. In this context, companies are challenged to design effective green marketing strategies that not only attract attention but also strengthen awareness and translate it into purchasing decisions. This study aims to examine the influence of green advertising, green perceived value, and price perception on green product purchasing decisions, with environmental awareness positioned as a mediating variable.Methodology: This study employed a quantitative associative approach using a survey method. The population consisted of consumers in West Java Province who had purchased environmentally labeled products within the past year. A purposive sampling technique was applied, resulting in 200 valid respondents. Data were collected through an online questionnaire and analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with SmartPLS 4 software.Findings: The results indicate that green advertising, green perceived value, and price perception each have a positive and significant effect on environmental awareness. Furthermore, environmental awareness significantly influences purchasing decisions for eco-friendly products. Mediation analysis confirms that environmental awareness serves as a psychological mechanism linking green marketing variables to purchasing decisions.Conclusion: These findings highlight the central role of environmental awareness in translating green marketing strategies into sustainable purchasing behavior. The study underscores the importance of credible green communication, clear articulation of ecological value, and fair pricing strategies in fostering long-term sustainable consumption.